1979
DOI: 10.1172/jci109628
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urine Polyamines in Normal and in Short Children

Abstract: A B S T R A C T The serum and urine polyamines putrescine, spermidine, and spermine were measured in 112 normal subjects from 0 to 70 yr of age, and in three groups of short children from 7 to 20 yr: 21 growth hormone (GH) deficient patients, 20 normal variant short stature children, and 9 girls with 45, X Turner's syndrome. Urine polyamines were expressed as micromoles per gram of creatinine or per kilogram body weight, and serum polyamines were expressed as nanomoles per milliliter.In normals, the three poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…The normal serum and urine levels of Pu, Sd, and Sm conformed to the previously described normal range (13). Normal levels of Cd in serum and urine were: 0.00-0.02 ,umol/liter and 0.17-0.93 ,mol/kg per BW per 24 h, respectively.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…The normal serum and urine levels of Pu, Sd, and Sm conformed to the previously described normal range (13). Normal levels of Cd in serum and urine were: 0.00-0.02 ,umol/liter and 0.17-0.93 ,mol/kg per BW per 24 h, respectively.…”
Section: Introductionsupporting
confidence: 82%
“…In the four men with MMD, serum and urine polyamine profiles differed from the normal controls in this study and in previously reported experiments (13). In serum and urine, Sm and Cd were significantly elevated (P < 0.005) and Sd was significantly depressed (P < 0.05).…”
Section: Introductioncontrasting
confidence: 65%
See 3 more Smart Citations